2012
DOI: 10.1186/1743-422x-9-304
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of IgG antibody to cytomegalovirus (CMV) after birth and seroprevalence of anti-CMV IgG in Chinese children

Abstract: BackgroundPrevalence of cytomegalovirus (CMV) infection is 90–100% in developing countries; however, the kinetics of anti-CMV IgG in infants remains elusive.MethodsSera from 112 mother-newborn pairs and longitudinal samples from 41 infants up to 2-year old were tested for anti-CMV IgG and IgM. Additionally, samples from 837 healthy children were included.ResultsOf 112 mothers, 108 (96.4%) were anti-CMV IgG positive; their 108 newborns were also seropositive. In a 2-year follow-up among 40 infants of positive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 28 publications
4
35
2
Order By: Relevance
“…Our findings from the pregnant women in Jiangsu province, having comparable economical status and residential density, were in accordance with the previous study conducted in Beijing, China, where the prevalence of anti-CMV IgG and IgM in 4692 childbearing-age or pregnant women was 92.5% and 1.8% respectively [6]. The seroprevalence in the current study is also comparable to that (96.4%) in pregnant women from Nanjing, the capital of Jiangsu province [19]. Thus, the high seroprevalence indicates that CMV infection is now universal in Chinese pregnant women.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings from the pregnant women in Jiangsu province, having comparable economical status and residential density, were in accordance with the previous study conducted in Beijing, China, where the prevalence of anti-CMV IgG and IgM in 4692 childbearing-age or pregnant women was 92.5% and 1.8% respectively [6]. The seroprevalence in the current study is also comparable to that (96.4%) in pregnant women from Nanjing, the capital of Jiangsu province [19]. Thus, the high seroprevalence indicates that CMV infection is now universal in Chinese pregnant women.…”
Section: Discussionsupporting
confidence: 91%
“…At 24 weeks, Ͻ20% of infants had IgG of high avidity, which could represent either transplacentally acquired maternal antibody or already mature infant antibody from primary infection. Our results indicate that most maternal antibody has waned by 6 months, consistent with a study from China suggesting that the maternally acquired anti-CMV IgG in infants disappears before 8 months of age (24); similarly, a study from Germany concluded that maternal antibody against CMV decayed by 12 months (25).…”
Section: Discussionsupporting
confidence: 79%
“…Human cytomegalovirus (HCMV) is a ubiquitous, highly hostspecific herpesvirus that causes severe, sometimes life-threatening disease in congenitally infected newborns as well as in immunocompromised individuals such as bone marrow allograft transplant recipients and AIDS patients (Boeckh and Geballe, 2011;Chen et al, 2012).The ability to reactivate with high viral load from latency in immunocompromised or immunosuppressed hosts endowed HCMV with high pathogenesis (Slobedman et al, 2004). To date, no effective vaccine or antiviral drugs is available to prevent or treat HCMV infection.…”
Section: Introductionmentioning
confidence: 99%